The use of the term compliance in order to improve the efficiency of companies - Iksanov Ilya Samatovich; Panova Elena Pavlovna; Frolova Natalia Nikolaevna; Filimonova Natalia Yuryevna; Shanin Andrey Aleksandrovich (SHS Web of Conferences, 2021)
The purposes of the study are: to reveal the meaning of the term “compliance”; to define the use of the term “compliance” in the Russian environment; to determine how the term “compliance” functions in Russian legislation; to find out what different definitions, functions, and scope of use of compliance can be found in the legal field. The article discusses the importance of compliance in various fields: legal, economic, and management. In Russian legislation, the definition of the term “compliance” is not disclosed or applied more locally. Based on the Russian and Western definitions of the concept, this article offers an interpretation of the “compliance” definition. The article analyzes compliance procedures that should not only monitor compliance with current legislation, but also act as a risk-oriented model and take into account factors that affect the implementation of any type of economic activity. In order to reduce possible business risks and comply with legislation on the part of organizations, and to address the issue of responsibility of entrepreneurs on the part of state control and Supervisory authorities, it is necessary to implement a compliance system. The main principles for implementing compliance control are also highlighted. Compliance control should apply not only to a legal entity and its structural elements, but also to a group of individuals. The implementation of compliance control is important not only for business entities, but also for state control and Supervisory organizations, since compliance control allows you to determine the integrity of a business in carrying out its commercial activities, and is also a mitigating circumstance in determining responsibility and punishment.